Chatbot Design to Help Learners Self-Regulte Their Learning in Online Learning Environments - Kaiss, Wijdane; Mansouri, Khalifa; Poirier, Franck (2023 IEEE International Conference on Advanced Learning Technologies (ICALT), 2023)
E-learning environments are part of the self-learning ecosystem of which self-regulation is one of the main pillars. One of the key factors contributing to dropping out in an e-learning environment is the lack of self-regulatory skills. This skill is often absent in many learners, leading them to abandon their training. In this paper we propose a methodology, chatbot architectural design, allowing to help the learner to self-regulate in his/her learning by supporting him/her through a chatbot within the Moodle platform, which constitutes a metacognitive virtual assistant, to provide metacognitive messages. The aim is to improve the quality of learning in the e-learning environment.